Analisis Hukum Terkait Piercing The Corporate Veil dalam Perkara Penundaan Kewajiban Pembayaran Utang / PKPU - Saka Triawan (UNES Law Review, 2023)
In running its business activities, a company in the context of the laws of the Republic of Indonesia must have at least 3 (three) main organs, namely the Board of Directors, Board of Commissioners, and General Meeting of Shareholders. Each organ of the Company also has its own responsibilities as regulated in the articles of association of the Company and the Statutory Regulations that regulate it so that when losses occur to the Company, both material and immaterial, the organ is responsible in accordance with their authority to act for and on behalf of the Company, but in certain circumstances, this limited liability can be waived or eliminated as known in the doctrine of Piercing The Corporate Veil. Proving the existence of losses caused by the Company's organs is quite difficult to do because of the inherent position actions of each of the Company's organs. On the other hand, in cases of Bankruptcy and Suspension of Payment where the proof must be simple, the Piercing the Corporate Veil doctrine is often difficult to apply because it is difficult to identify whether a loss to the Company was actually caused by the Company's organs themselves and not based on the Company's actions permitted according to the articles of association and Statutory Regulations.